Physicochemical stability, antioxidant activity, and antimicrobial activity of quercetin-loaded zein nanoparticles coated with dextrin-modified anionic polysaccharides. (30th July 2023) - Zhang, Zhiheng; Hu, Yao; Ji, Hangyan; Lin, Qianzhu; Li, Xiaojing; Sang, Shangyuan; Julian McClements, David; Chen, Long; Long, Jie; Jiao, Aiquan; Xu, Xueming; Jin, Zhengyu; et al.
Highlights: ZCNPs with core–shell biopolymer nanoparticles were assembled by a simple method. Main source of raw material for ZCNPs preparation is maize processing byproducts. Quercetin-ZCNPs exhibit good biological activity and physicochemical stability. A valuable reference for the oral utilization of hydrophobic nutraceuticals. Abstract: Core-shell biopolymer nanoparticles are assembled from a hydrophobic protein (zein) core and a hydrophilic polysaccharide (carboxymethyl dextrin) shell. The nanoparticles were shown to have good stability and the ability to protect quercetin from chemical degradation under long-term storage, pasteurization, and UV irradiation. Spectroscopy analysis shows that electrostatic, hydrogen bonding, and hydrophobic interactions are the main driving forces for the formation of composite nanoparticles. Quercetin coated with nanoparticles significantly enhanced its antioxidant and antibacterial activities and showed good stability and slow release in vitro during simulated gastrointestinal digestion. Furthermore, the encapsulation efficiency of carboxymethyl dextrin-coated zein nanoparticles (81.2%) for quercetin was significantly improved compared with that of zein nanoparticles alone (58.4%). These results indicate that carboxymethyl dextrin-coated zein nanoparticles can significantly improve the bioavailability of hydrophobic nutrient molecules such as quercetin and provide a valuable reference for their application in the field of biological delivery of energy drinks and food.